The Increasing Of Ginger Chips Production Capacity As The Effort To Fulfill The Market Demand - Endah Rahayu Lestari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2015)
ABSTRACTGinger chips is a kind of snack that made from ginger, shredded coconut, sesame seeds, and sugar. This product is similar to candy, but this product is produced inefficiently due to anual and traditional process. The purpose of this activity is to increase the production capacity of ginger chips at UKM Sona Jaya in Batu by applied the mechanical processing machines to fulfill the market demand. This acivity successfully introduced the washing machine for ginger tuber with the capacity of 5 kg ginger/process/5 minutes, shredding machine with the capacity of 1 piece coconut/minute, and roasting machine with the capacity 12 piece coconut/process/4 hours. It is also applied digital scales and continuous sealer. By this processing machines, it showed the increasing of efficiency and average production capacity as high as 25%. Keywords: digital scale, ginger chips, rhizome, roasting machine, shredder, washing machine